Communication strategies of cultural meaning and social values of Chinese historical dramas: A case study of Zhuangzi playing with his wife - Jingjing, Wang; Klaysung, Somsak (Edelweiss Applied Science and Technology, 2025)
This study examines the communication strategies of Chinese historical dramas in conveying cultural meaning and social values, using "Zhuangzi Playing with His Wife" as a case study. Employing a mixed-methods approach, including documentary research, thematic analysis of focus groups (n=30), and structural equation modeling of survey data (n=620), qualitative findings reveal three central themes: the role of cultural heritage in fostering pride, emotional resonance as a bridge to historical narratives, and tensions between traditional values and modern identity critiques. Quantitative results demonstrate strong audience alignment with the drama’s social value messaging (M=4.33) and emotional impact (M=4.22), though acceptance scores were lower (M=3.74), reflecting generational divides. The validated structural model (CFI=0.95, RMSEA=0.047) highlights cultural heritage as a key driver of emotional and moral engagement (β=0.64–0.75). The study concludes that historical dramas serve as dynamic cultural mediators but must balance idealized narratives with critical inclusivity to address contemporary complexities. Its novelty lies in integrating mixed methods to dissect both affective and cognitive audience responses, offering theoretical insights into cultural transmission and practical implications for creators: prioritizing emotionally resonant storytelling while integrating marginalized perspectives. This research advances discourse on media’s role in heritage preservation amid globalization, advocating for narratives that honor tradition yet invite reflective dialogue.